Temporal Trend of Age at Diagnosis in Hypertrophic Cardiomyopathy: An Analysis of the International Sarcomeric Human Cardiomyopathy Registry. (September 2020) - Canepa, Marco; Fumagalli, Carlo; Tini, Giacomo; Vincent-Tompkins, Justin; Day, Sharlene M.; Ashley, Euan A.; Mazzarotto, Francesco; Ware, James S.; Michels, Michelle; Jacoby, Daniel; Ho, Carolyn Y.; Olivotto, Iacopo
Abstract : Background: Over the last 50 years, the epidemiology of hypertrophic cardiomyopathy (HCM) has changed because of increased awareness and availability of advanced diagnostic tools. We aim to describe the temporal trends in age, sex, and clinical characteristics at HCM diagnosis over >4 decades. Methods: We retrospectively analyzed records from the ongoing multinational Sarcomeric Human Cardiomyopathy Registry. Overall, 7286 patients with HCM diagnosed at an age ≥18 years between 1961 and 2019 were included in the analysis and divided into 3 eras of diagnosis (<2000, 2000–2010, >2010). Results: Age at diagnosis increased markedly over time (40±14 versus 47±15 versus 51±16 years, P <0.001), both in US and non-US sites, with a stable male-to-female ratio of about 3:2. Frequency of familial HCM declined over time (38.8% versus 34.3% versus 32.7%, P <0.001), as well as heart failure symptoms at presentation (New York Heart Association III/IV: 18.1% versus 15.8% versus 12.6%, P <0.001). Left ventricular hypertrophy became less marked over time (maximum wall thickness: 20±6 versus 18±5 versus 17±5 mm, P <0.001), while prevalence of obstructive HCM was greater in recent cohorts (peak gradient >30 mm Hg: 31.9% versus 39.3% versus 39.0%, P =0.001). Consistent with decreasing phenotypic severity, yield of pathogenic/likely pathogenic variants at genetic testing decreased over time (57.7% versus 45.6% versus 38.4%, P <0.001). Conclusions: Evolving HCM populations include progressively greater representation of older patients with sporadic disease, mild phenotypes, and genotype-negative status. Such trend suggests a prominent role of imaging over genetic testing in promoting HCM diagnoses and urges efforts to understand genotype-negative disease eluding the classic monogenic paradigm.